Pengaruh Ownership Structure Terhadap Firm Value Pada Perusahaan Manufaktur yang Terdaftar di Bei - Kevin Lesmana; Sany Sany (Business Accounting Review, 2021)
his study aims to analyze the effect of ownership structure on firm value in ManufacturingCompanies Listed on the IDX. This study uses data from 2016-2020, and the analysis technique usedis multiple linear regression of panel data using Gretl software. The results showed that familyownership had a significant positive effect on firm value, institutional ownership had no effect onfirm value, and government ownership had a significant positive effect on firm value. This studyuses the control variables leverage, firm size and profitability, the results of the control variablesindicate that leverage and firm size had no effect on firm value and profitability affect firm value inManufacturing Companies Listed on the IDX.